2016
DOI: 10.1016/j.bar.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Strategic cost management and performance: The case of environmental costs

Abstract: a b s t r a c tDespite recent developments in the stream of research devoted to strategic cost management (SCM), there are limitations found with this research, notably the overemphasis on one component of SCM (executional cost management), the underemphasis on the other component (structural cost management), the insufficiency of links between those two components, and the absence of evidence supporting their link with performance. The aim of this study is to examine the relationship between both components o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 76 publications
(97 reference statements)
2
57
1
7
Order By: Relevance
“…Henri et al (2016) also found a direct relationship between the tracking of environmental expenditures and financial performance [62]. They suggest that greater transparency and accuracy of waste and environmental information, in turn, improve managerial decision making, and leads to improved financial performance.…”
Section: Relationship Between Waste Reduction Targets and Firms' Profmentioning
confidence: 95%
See 3 more Smart Citations
“…Henri et al (2016) also found a direct relationship between the tracking of environmental expenditures and financial performance [62]. They suggest that greater transparency and accuracy of waste and environmental information, in turn, improve managerial decision making, and leads to improved financial performance.…”
Section: Relationship Between Waste Reduction Targets and Firms' Profmentioning
confidence: 95%
“…Waste reduction has continued to be a significant problem in the current century, and it is not surprising to observe that financial managers worldwide consider the reduction of these costs to be a critical sustainability driver (Wilburn & Wilburn, 2013;Henri et al, 2016;Hornsby et al, 2016) [19,61,62]. Wang et al (2014) indicate that companies with environmental expenditures were significantly more productive than companies without environmental expenditure [63].…”
Section: Relationship Between Waste Reduction Targets and Waste Managmentioning
confidence: 99%
See 2 more Smart Citations
“…The paper industry must pay more attention to knowledge on how much global warming gases and other emissions its sites are contributing to soil, air and water [55]. Henri et al [56] address that the environmental costs aimed at managing, controlling, and optimizing costs for a given environmental strategy. These environmental costs have an impact on the product design, such as raw material composition and operational product design.…”
Section: Emission and Sustainability Measuring And Calculationsmentioning
confidence: 99%